Becoming Organic: Nature and Agriculture in the Indian Himalaya - Seshia Galvin, Shaila (Yale University Press, 2024)
Book abstract Becoming Organic traces the social and bureaucratic life of organic quality, yielding fresh understandings of the meaning and practice of organic and sustainable agriculture. Decentering perspectives on organic farming that rely on the specific historical experiences of Europe and North America, the book examines how certified organic farming is introduced in the Himalayan state of Uttarakhand in northern India. Organic quality, the book argues, is best understood less as a material property of land or its produce than as something that is diffusely produced; it takes shape across discursive, regulatory, and affective registers, through practices that encompass producing compost as well as certification records; inspecting fields, grains, and documents; and reimagining relationships between the state, market, and agricultural producers on a rural frontier. This conceptually innovative and methodologically original ethnographic study shows how the development of organic agriculture in Uttarakhand is historically and regionally situated in broader and enduring relations between nature and agriculture that have been shaped by layered histories of colonialism, postcolonial development, and neoliberal reform. It reveals how, during a time of great political change and economic liberalization, development practice unfolds in rural India through complex relations forged among state authorities, private corporations, and new agrarian intermediaries. Introduction: Remaking the Agrarian on a Himalayan Frontier The introduction examines how organic agriculture became a crucible for reimagining and remaking the agrarian in the state of Uttarakhand, a region where, for much of the nineteenth and twentieth centuries, agriculture was deemed backward and undeveloped. Organic, it argues, should be understood and studied as a quality that must be assembled, rather than as a distinctive physical, sensory, or material property of land and its produce. It proceeds to set out a framework to provincialize organic, proposing to study organic quality as emergent in historically situated social, cultural, economic, and political practices and relations. In Uttarakhand this entails, first, paying attention to the intersection of organic agriculture with political and economic reforms in India after liberalization; second, it necessitates inquiry into how rural cultivators exercise agency and experience subjectivity through organic farming; finally, it probes how organic agriculture reworks notions of modernity and tradition, nature and agriculture, that powerfully inform understandings of human-environment relations in the Indian Himalaya and beyond. As it relates the making of organic quality to processes of state-making and post-reform development, the introduction affords new insights into the production of agricultural commodities and agrarian relations. Fertile Ground Soil has long been at the center of debates about environmental degradation in the Himalaya. This chapter shows how concern about the care of soil entwines understandings of human and nonhuman agency with practices of state-making in the region. Moving between colonial efforts to assess the fertility of land, and contemporary interventions that encourage farmers to construct compost pits, this chapter demonstrates that the ways in which agrarian practices of working with soil, manure, and compost are recognized by state institutions powerfully inform development interventions. Introducing the concept of agrarian agency, the chapter parses this notion, dwelling on distinctions drawn by state officials between being “organic by default” and becoming “organic by design.” It argues that in the twenty-first century, the particular ways in which agrarian agency gets parsed prove to be consequential both for who can become organic, and for what organic itself comes to mean. Ultimately, this chapter shows that what comes to count as human agency, and what does not, is itself a mode through which state power works. The Limits of Transparency and the Farming of Trust Focusing on the farming of certified organic basmati rice in Uttarakhand’s Doon Valley, this chapter examines the relationship between transparency and trust in certification processes. Certification, it is often claimed, affords transparent knowledge about its objects. Because of this, it is thought to be necessary for generating and maintaining widespread public trust. This chapter explores the limits of transparent knowledge, arguing that as organic agriculture becomes established under state government auspices in the Doon Valley, trust is neither solely emergent in personalized relations nor simply an outcome of certification processes. Instead, this chapter shows how practices of organic certification, under conditions of limited transparency, shape and fundamentally reconfigure trust. Through fine ethnography that focuses on sentiments of trust, belief, or faith, expressed by certification inspectors during the course of their work, the chapter traces how such sentiments become integral to the making—and the meaning—of certified organic farming. Becoming Basmati Under contract farming arrangements for organic agriculture introduced in the early 2000s in Uttarakhand’s Doon Valley, the production of organic basmati rice must adhere not only to standards for organic production and certification but, simultaneously, to standards for export-quality basmati rice that pertain to the physical and material features of the grain itself. This chapter shows how the coming into being of organic basmati rice has been shaped not only by the standards and practices of organic agriculture and certification, but also by the conditions of contract farming established in the Doon Valley in the early 2000s by means of the longer histories of commoditization through which basmati has become a globally traded grain. The chapter examines the convergence of sociotechnical and socionatural practices that have made basmati a distinct category of rice—a category brought into being through government notifications, geographic indications, processes of standardization and commodification that, while established far from the Doon Valley where basmati is cultivated, are enacted and realized every day in its fields. Market Imaginaries and the Horizons of Aspiration This chapter turns from the basmati fields of the Doon Valley to Uttarakhand’s mountainous regions, in order to explore how organic quality catalyzes imaginations of new agricultural markets for little-known hill crops. Imagination and aspiration are here taken to be forms of affect and elements of human agency that are central to forging new market connections. The analysis departs from understandings of economic agency as primarily calculative, an approach characteristic of both recent behavioral and actor-network approaches. The chapter considers the ways in which different kinds of aspiration and imagination encounter each other, and are negotiated, in the context of buyer-seller meets that bring hill cultivators together with potential commercial buyers. It then examines the forms of bureaucratic imagination through which organic agricultural production in the mountains is made amenable to the supply-chain logistics of metropolitan and international buyers. Finally, it turns to the village of Nagthari in western Uttarakhand and examines how its residents aspire and act to cultivate new forms of market participation. Exhibiting Organic Uttarakhand This chapter explores how brand-building and state-making intertwine in neoliberal development practice. It examines how the brand “Organic Uttarakhand” established by the Uttarakhand Organic Commodity Board attached itself not just to pulses, grains, and spices produced by organic farmers, but how it became a signifier for the region itself. To make this argument, the chapter considers three distinct trade fairs and exhibition spaces in which the Board participated in 2007 and 2008. These exhibitions proved to be crucial sites in which the promotion of organic agriculture was linked with efforts to build the state’s brand equity as “Organic Uttarakhand.” The circulation of discursive and material artifacts—signs, posters, and brochures as well as agricultural products from the mountains—constituted organic quality through an exhibitionary complex, and helped produce Uttarakhand as an organic state. At the same time, abiding social imaginaries of Uttarakhand as a place of nature and an abode of the gods were also conjured in these domains in order to endow organic products with a singular authenticity as they circulated through new market channels. Epilogue: Promises of Transformation The epilogue offers an account of the ways in which organic agriculture has unfolded in Uttarakhand in the years since ethnographic fieldwork was undertaken in 2007 and 2008. It reflects on what organic means, and to whom its greatest promise extends, considering the ways in which social and caste position, education, and economic status shape the extent to which different cultivators have engaged with the work of becoming organic. The epilogue places the study of organic agriculture in Uttarakhand in conversation with the rapidly rising interest in sustainable agriculture, the “green economy,” and debates about contemporary agrarian transitions. By showing how organic should be understood as a diffusely produced quality, rather than a material property or essence, it charts a course for expanded understandings of how agricultural commodities come into being.